Improving Community Competence in Environmental Health Management: A Health Education Literacy Review - Lyna M. N. Hutapea; Dwight Mahaputera Marulitua Hutapea (Oshada, 2024)
Inadequate community competence in managing environmental health remains a pressing issue across many regions, including Indonesia. This challenge underscores the critical need for comprehensive insights into how health education can play a pivotal role in empowering communities. This research delves into an in-depth systematic literature review, aiming to dissect and assess diverse strategies employed in health education programs to boost the efficiency of environmental health management initiatives. Utilizing the Systematic Literature Review (SLR) approach, this study adheres to the framework provided by PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). The process encompasses key phases: defining precise research inquiries, determining rigorous inclusion and exclusion parameters, and executing an extensive literature search through prominent academic databases such as Google Scholar, PubMed, and Scopus. The search leveraged specific keywords, including "Community Health Education," "Competency in Environmental Health Management," and "Impactful Health Education Programs." From an initial pool of 239 publications, only 25 articles satisfied the stringent screening criteria. The consolidated findings reveal that health education models that are systematically designed, foster active community involvement, and are tailored to local needs significantly enhance public awareness, shape positive attitudes, and develop practical skills for environmental health management. These insights offer actionable strategies to refine and strengthen health education programs across diverse settings.